Prospects of Digitalization of MSMEs Business Expansion in Sepakat Village - Yohanes Kuleh; M. Amin Kadafi; Zainal Ilmi (International Journal of Social Science and Business, 2023)
As an innovation in the field of technology and communication, the development of the internet in Indonesia continues to increase every year. The development of increasingly sophisticated technology causes this with the many features of online buying and selling applications. This study aims to analyze the obstacles and constraints of Micro, Small and Medium Enterprises (MSMEs) in joining online stores, considering the development of the internet and increasingly sophisticated technology. The type of research used is qualitative observation with the object of research being Agreed Village, a assisted village of the Faculty of Economics and Business, Mulawarman University. Agreed Village was chosen because of the large number of MSMEs in the inland fisheries sector and is part of MSMEs in Kutai Kartanegara Regency. Data was collected through interviews with respondents who had experience in using or not using online stores. The data is then analyzed qualitatively. The main result of this study is the identification of obstacles and obstacles faced by MSMEs in joining online stores. The conclusion of this study is that the ease and efficiency of online transactions are the main factors in people's preferences in using online stores. The implication of this research is the importance of online business digitalization development strategies for MSMEs by considering the principles of good business rules and ethics.